Astrocytic HMGCR-Mediated Cholesterol Alleviated Parkinson’s Disease Phenotypes by Inhibiting NF-κB Neuroinflammation - Xiaofeng Tian; Qing Liu; Jiacheng Zhang; Huijiao Du; Zhaoran Wei; Linjie Sun; Jiamin Gao; Ruiting Zhao; Lei Wang; Yizhou Zhang (Molecular Neurobiology, 2026)

Construction of built-in electric field in Ru/Vo-NiCo2O4 heterostructure for efficient ethylene glycol oxidation reaction coupled nitrate to ammonia electrolysis - Jingwen Ma; Ruiting Wang; Jinhao Liu; Ying Tian; Junbin Li (Journal of Environmental Chemical Engineering, 2025)

Preparation of AuSe-BNPs/CFME and its high-sensitivity simultaneous detection of caffeic acid and dihydrotanshinone I - Han Cheng; Yanbing Pan; Tao Fang; Uchkun Ishimov; Awais Ihsan; Abrar Hussain; Ruiting Tian; Wenwen Ma; Jun Li; Xianju Huang (Chemical Engineering Journal, 2025)

Ubiquitin-conjugating enzyme E2T confers chemoresistance of colorectal cancer by enhancing the signal propagation of Wnt/β-catenin pathway in an ERK-dependent manner - Bo Liu; Ruiting Liu; Xiaolong Zhang; Lifei Tian; Zeyu Li; Jiao Yu (Chemico-Biological Interactions, 2025)

A photoelectrochemical aptasensor for omethoate determination based on a photocatalysis of CeO2@MnO2 heterojunction for glucose oxidation - Xingyang Wu; Jing Zhu; Ruiting Wen; Jiuying Tian; Jusheng Lu (Analytica Chimica Acta, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)